Sustainable Development Indicator Systems for Island Cities: The Case of Zhoushan Maritime Garden City - Qianhu Chen; Hanning Dong (Island Studies Journal, 2019)
Because islands and archipelagos are often said to present distinct characteristics, there is a need to develop indicator systems for guiding and evaluating the sustainable development of island cities. This methodologically oriented study considers existing standards for urban sustainable development and uses these as the basis for selecting 70 indicators to assess the sustainability of China’s Zhoushan Archipelago, bearing in mind Zhoushan’s specific island and archipelago environment. The indicators are classified into ecological, social, economic, cultural, and scientific and technological dimensions. Present conditions in Zhoushan Archipelago are evaluated using statistical data. The results shows that the sustainability of Zhoushan’s ecology, economic and social performance is good, while the cultural and science and technology dimensions perform relatively poorly. This study suggests future focus areas for Zhoushan’s urban sustainable development as a maritime garden city.